SPECIFICUL CORELAŢIONAL AL CUNOAŞTERII CA BAZĂ A INOVĂRII - USM ADMIN (Moldova State University, 2011)
The objectives of innovational strategies in Republic of Moldova are based on overall objectives of EU, strategies and policies that are applied in EU member states; experience analysis of most developed countries, which offer a chance to launch innovative activities in the system of higher education from Republic of Moldova. The knowledge society provides social and axiological connotation for education, knowledge sector is dependent on education opportunities. In this situation, the knowledge factor is in production process of knowledge.